2003
DOI: 10.1046/j.1439-0434.2003.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Carla‐ and Potyviruses from Narcissus in China

Abstract: Conserved carlavirus and potyvirus primers were used in reverse transcriptase‐polymerase chain reaction (RT‐PCR) to amplify virus fragments from Chinese narcissus (Narcissus tazetta var. chinensis) in China and the fragments were subsequently sequenced and compared in phylogenetic analyses. Samples from Fujiang province and Shanghai contained either one or two potyviruses and a carlavirus. One potyvirus (PY1) showed a distant relationship to Iris severe mosaic virus, Onion yellow dwarf virus and Shallot yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 6 publications
4
26
0
Order By: Relevance
“…Conversely, the central and the C-terminal regions (from 49 to 319 aa) are highly conserved in all isolates (data not shown). The presence of conserved domains such as Flexi_CP_N and Flexi_CP had been previously reported in CP of carlaviruses and potexviruses [7]. In the present study, the presence of 13 different conserved domains and of 3 motifs within the CP were predicted using SMART [8] and MEME [9] programs, respectively (Suppl.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Conversely, the central and the C-terminal regions (from 49 to 319 aa) are highly conserved in all isolates (data not shown). The presence of conserved domains such as Flexi_CP_N and Flexi_CP had been previously reported in CP of carlaviruses and potexviruses [7]. In the present study, the presence of 13 different conserved domains and of 3 motifs within the CP were predicted using SMART [8] and MEME [9] programs, respectively (Suppl.…”
supporting
confidence: 52%
“…CP gene sequences could also group viruses of genus Carlavirus in two distinct phylogenetic subgroups. A similar sub grouping of Carlavirus species could also be shown when other genomic regions, i.e., nucleic acid binding protein and replicase genes, are used [7,18,19].…”
mentioning
confidence: 60%
“…The concats were used for evolutionary analyses. The corresponding regions of two sequences of Japanese yam mosaic virus (JYMV) Nakamae 1999, 2000), one of Scallion mosaic virus (ScMV) and one of Narcissus yellow stripe virus (NYSV) (Chen et al 2003) were used to align the TuMV concats as reported earlier (Tomimura et al 2004;Tomitaka and Ohshima 2006). We thus aligned all 62 P1 sequences with those of two JYMV isolates as the outgroup, the R12+Pro sequences with those of JYMV and ScMV, and the CP sequences with that of NYSV using Clustal X (Jeanmougin et al 1998).…”
Section: Recombination Analysesmentioning
confidence: 99%
“…The calculated trees were displayed by TREEVIEW (Page 1996). One ScMV and two JYMV sequences were used as the outgroup to construct a phylogenetic tree of the concats, because only the CP sequence of one NYSV isolate was available (Chen et al 2003). The JYMV and ScMV sequences corresponding to individual gene regions within the concats were aligned using their encoded amino acids as described, then reassembled to form sequences 2,979 nt long.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…One of these is the ‘TuMV group’, which comprises TuMV and at least five other species, all from monocotyledonous plants. These include Japanese yam mosaic virus (JYMV) [10], [11], Narcissus yellow stripe virus (NYSV) [12], and Scallion mosaic virus (ScMV) [13], all known from full genomic sequences. Sequence analyses of the coat protein have shown that the TuMV group also contains Indian narcissus potyvirus and Narcissus late season yellows potyvirus.…”
Section: Introductionmentioning
confidence: 99%